Heusler Alloys Properties, Growth, Applications - Felser, Claudia; Hirohata, Atsufumi (Springer Series in Materials Science, 2016)
This book gives an overview of the physics of Heusler compounds ranging from fundamental properties of these alloys to their applications. Especially Heusler compounds as half-metallic ferromagnetic and topological insulators are important in condensed matter science due to their potential in magnetism and as materials for energy conversion. The book is written by world-leaders in this field. It offers an ideal reference to researchers at any level.